Analysis of traffic flow characteristics in a university setting - Kadar Hamsa, Abdul Azeez (2011)
University campuses should create peaceful and pleasant learning environment for the benefits of campus community. The degree of transport use on-campus by both staff and student population is very important to achieve this required but vital target. It has been observed in the recent past that the alarming vehicle growth in the University would eventually not only exert tremendous pressure on the road and other traffic related infrastructure but also induce detrimental effects on learning environment. The purpose of this paper is to analyse the existing traffic flow characteristics especially traffic volume, vehicle growth, road and other traffic related infrastructure in International Islamic University Malaysia (IIUM), Gombak campus. Inventory survey was administered to collect information related to road geometrics and traffic circulation system. Traffic volume at the selected stations along the major road in IIUM was collected by field survey. Additionally, questionnaire survey was administered to ascertain perceptions on existing traffic circulation system on-campus among IIUM community. The findings on traffic flow characteristics in IIUM, Gombak campus are described in this paper. Discussion on issues related to traffic flow on-campus and conclusions are also drawn.